A descriptive analysis of academic engagement and collaboration of students with autism during elementary computer science. Issue 4 (1st October 2020) - Israel, Maya; Chung, Moon Y.; Wherfel, Quentin M.; Shehab, Saddeddine
ABSTRACT: Background and Context: Elementary computer science (CS) can be engaging and challenging for some students with disabilities who struggle with complex problem solving. Objective: This study examined academic engagement of students with autism spectrum disorder (ASD) in elementary CS instruction. Method: A mixed methods case study was used to study how three elementary students with ASD participated in CS instruction that involved a peer collaboration strategy. Findings: All students were engaged with the computational tasks, with variations in academic engagement. All experienced challenges with the computing activities that resulted in disengagement or limited independent problem solving. Students received "in the moment" supports, with little evidence of planned instructional scaffolding. Implications: Students did not receive individualized support. With such supports, they may have had a more positive experience. It is important to continue to study the experiences of students with disabilities during elementary CS instruction to better support these learners.